IJTIHAD SEBAGAI KONSEP PEMBARUAN HUKUM ISLAM - Sudirman Suparmin (Universitas Islam Negeri Sumatera Utara Medan, 2016)
Ijtihad As the concept of Islamic Law Reform. Ijtihad is modernist era, the problems that arise would require precise and accurate answers to avoid unrest beings who need peace in charity. The presence of the mujtahid of course is expected to guide and direct the brightness while providing for the people. so that the deeds of worship performed by people completely avoid the error. Ijtihad as the concept of reform in Islamic law is indeed relevant to the advancement of the Muslims, so avoid stagnation and blindness in charity. And ijtihad as the concept of reform is certainly the idea of progress for Muslims, in accordance with the principles of Islamic law rules Sholeh Li kulli Zamani wal al-Makani. Keyword: Ijtihad, Concept, Reform, Islamic law